(untitled) (KULT_online, 2025)
Representing Gender-Based Violence: Global Perspectives, edited by Caroline Williamson Sinalo and Nicoletta Mandolini, provides a critical analysis of gender-based violence from a global perspective. The volume analyzes how representations in media, art, politics, and popular culture can reinforce the patriarchal symbolic order, reveal invisible forms of abuse, and highlight the ethical and political challenges of such representations. Despite its comprehensive approach, the book lacks a general conclusion to synthesize findings across contexts.